2017
DOI: 10.1016/j.cmet.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Links BMP2 and TGFβ1 Pathways in Vascular Smooth Muscle Cells, Regulating Cell Proliferation and Glucose Metabolism

Abstract: BMP2 and TGFβ1 are functional antagonists of pathological remodeling in the arteries, heart, and lung; however, the mechanisms in VSMCs, and their disturbance in pulmonary arterial hypertension (PAH), are unclear. We found a pro-proliferative TGFβ1-Stat3-FoxO1 axis in VSMCs, and PPARγ as inhibitory regulator of TGFβ1-Stat3-FoxO1 and TGFβ1-Smad3/4, by physically interacting with Stat3 and Smad3. TGFβ1 induces fibrosis-related genes and miR-130a/301b, suppressing PPARγ. Conversely, PPARγ inhibits TGFβ1-induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
158
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(173 citation statements)
references
References 69 publications
15
158
0
Order By: Relevance
“…PPARγ expression was lost early during the adipocyte-myofibroblast transition and the PPARγ agonist rosiglitazone prevented this loss. This is in line with known anti-fibrotic effects of thiazolidinediones (TZDs) 20,25 . We observed that high PPARγ expression in a heterogeneous population of differentiated OP9 cells was correlated with the lack of transcriptional response to the profibrotic cytokine TGF-β.…”
Section: Discussionsupporting
confidence: 82%
“…PPARγ expression was lost early during the adipocyte-myofibroblast transition and the PPARγ agonist rosiglitazone prevented this loss. This is in line with known anti-fibrotic effects of thiazolidinediones (TZDs) 20,25 . We observed that high PPARγ expression in a heterogeneous population of differentiated OP9 cells was correlated with the lack of transcriptional response to the profibrotic cytokine TGF-β.…”
Section: Discussionsupporting
confidence: 82%
“…It is well known that Smurf2 can suppress the expression of Runx2 activity, a critical osteoblast‐specific transcription factor, which leads to decreasing in osteoblast formation . Several studies have clearly demonstrated that PPARγ is highly expressed in early stage of adipogenesis and plays a key role in adipocyte formation . We illustrated that miR‐130a promotes osteogenesis of BMSC by eliminating the effect of Smurf2 and acts as a negative regulator of adipogenesis of BMSC by directly targeting PPARγ.…”
Section: Discussionmentioning
confidence: 76%
“…39,40 Several studies have clearly demonstrated that PPARγ is highly expressed in early stage of adipogenesis and plays a key role in adipocyte formation. 44,45 We illustrated that miR-130a promotes osteogenesis of BMSC by eliminating the effect of Smurf2 and acts as a negative regulator of adipogenesis of BMSC by directly targeting PPARγ. These results indicated that miR-130a post-transcriptionally regulates Smurf2 and PPARγ expression at osteogenic and adipogenic differentiation process.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, peroxisome proliferator-activated receptor gamma (PPARγ) has been shown to bind STAT3 as well as Smad3 and inhibit TGFβ1-induced phosphorylation and nuclear translocation of both molecules. [199,200]. Treatment of fibroblasts with the PPARγ agonist, rosiglitazone, highlights potential alternative avenues to modulating profibrotic signaling, as it has been shown to significantly attenuate TGFβ1-mediated up-regulation of fibrotic markers Alpha-Actin-2 (ACTA2) and COL1A1 [201].…”
Section: Stat3 and Fibrosismentioning
confidence: 99%